Determinants of customer satisfaction towards broadband services in Malaysia - Ahmad Syakir Junoh @ Ismail; Mohd Rafi Yaacob (Vol. 1 No. 2; September 2011, 2011)
The aim of this research is to understand the customer satisfaction of broadband services in Malaysia with regards to price, speed and stability. Demographic factors in which consist of education, nationality, monthly income are moderator of the study. This research was conducted based on random sample of broadband users in Malaysia by using a questionnaire survey. Altogether 150 respondents in Klang Valley were surveyed for this study. The findings show that price, speed and stability have no significant relationship with customer satisfaction level on broadband in Malaysia. However, there are associations between education level and stability factors, monthly income level and price factors, nationality and price factors, gender and acceptable price level, monthly income and internet broadband usage period and gender and speed. This research provides a useful starting point to understand the customer satisfaction level of broadband services in Malaysia. The findings of the research may have implication for internet broadband service providers in enhancing their pricing strategy and improving their service particularly in speed and stability. Thus it will help Malaysian Government in encouraging and promoting the adoption and utilization of internet broadband to boost the economy.